การลดการปนเปื้อนของเชื้อจุลินทรีย์และการยืดอายุการเก็บรักษาของกะเพราและโหระพาด้วยสารละลายกรดอินทรีย์และน้ำฟองอากาศขนาดเล็ก - ดุสิดา หนูทอง (มหาวิทยาลัยสงขลานครินทร์, 2022)
Sweet basil and holy basil are the most widely used condiments around the world. However, Escherichia coli and Salmonella spp. contamination is a serious problem in the production process. The causes may come from harvesting, cleaning, packing, and logistic process. The primary objective of this study is to evaluate the efficacy of 1% lactic acid, 1% citric acid, and 1% fumaric acid onthe reduction of the total plate count, E. coli, and S.Typhimurium, compared with water and chlorinated water (100ppm). It was found that 1% fumaric acid had the best efficacy for decontamination. The secondary objective is to evaluate the efficacyof the 10minutes microbubble-1% fumaric acid combination for the reduction of total plate count, E. coli, and S.Typhimurium. For sweet basil, this technique can reduce the total plate count, E. coli, and S. Typhimurium by 3.03 log cfu/g, 3.08 lof cfu/g, and 2.98 log cfu/g, respectively. For holy basil, this technique can reduce total plate count, E. coli, and S. Typhimurium by 3.21 logcfu/g, 4.65 lof cfu/g, and 3.98 log cfu/g, respectively. After decontamination with the 10 minutes icrobubble-1% fumaric acid combination, sweet basil and holy basil were preserved in a pored-LDPE bag at 12±1 ◦C for 6 days. Sweet basil preserved with this technique had less total plate count than a non-decontaminated group. However, the experimental group had more percentage of weight loss and percentage of browning. Similar results were observed in holy basil. No statistical significance in chlorophyll content changing or electrolytes loss. Appearance, color, and odor were evaluated by a sensory test. The results of a sensory test reveal that non-decontaminated sweet basil and holy basil can be preserved for 4 days. However, disappointing results for decontaminating group, sweet basil can be preserved for 2 days and only 1 day for holy basil, as a result of the browning effect. In conclusion, using only 1% fumaric acid or the 10 minutes microbubble-1% fumaric acid combination can reduce the total plate count for sweet basil and holy basil, effectively. However, causing shorter shelf life due to unfavorable effects on the appearance.